Design And Analysis Of Gas Turbine Blade - V Nagabhushana Rao; P Vijaya Kumar; S.Hemaltha; I Mohan Rao (Elementary Education Online, 2023)
This research work will design and stress evaluate a jet engine turbine blade. A study on the use of novel materials is needed. The current study used Inconel 718 and Titanium T-6 as turbine blade materials. The influence of temperature and induced stresses on the turbine blade has been studied. A thermal analysis was performed to determine the direction of temperature flow caused by thermal loading. The turbine blade's tensions, shear stresses, and displacements developed due to the coupling effect of heat, and centrifugal loads were investigated structurally. The findings of two materials are compared to indicate the optimal material for a turbine blade (Inconel 718 and titanium T6). Based on the plots and results, Inconel718 is the best material since it is cheaper and has better qualities at higher temperatures than TitaniumT6.